2020
DOI: 10.1016/j.amjmed.2020.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Getting Unstuck: Challenges and Opportunities in Caring for Patients Experiencing Prolonged Hospitalization While Stable for Discharge

Abstract: Many physicians care for patients who remain in the hospital for prolonged periods despite being "medically ready" or stable for discharge. However, this phenomenon is not well-defined, and optimal strategies to address the problem are not known. A prolonged hospitalization past the point of medical necessity can harm patients, frustrate care teams, and is costly for the health care system. In this perspective, we describe opportunities to improve value of care for these patients through the lens of the Quadru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…Consistent with prior research, 7,12 our study also showed that a small subset of patients (ie, the prolonged hospitalization cohort, ∼2% of overall discharges) is responsible for a disproportionate number of our overall bed days of care (∼23%). Thus, efforts targeted at reducing LOS for these patients are necessary and appropriate.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with prior research, 7,12 our study also showed that a small subset of patients (ie, the prolonged hospitalization cohort, ∼2% of overall discharges) is responsible for a disproportionate number of our overall bed days of care (∼23%). Thus, efforts targeted at reducing LOS for these patients are necessary and appropriate.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with other studies, our results confirm the importance of system-level and multi-pronged approaches to overcome discharge delays. 2,14 Our findings have several implications. First, although UAE hospitals routinely track length of stay, recognition of delayed discharges due to non-medical barriers can help identify inefficient processes and encourage interventions that improve discharge planning.…”
Section: Implications and Conclusionmentioning
confidence: 81%
“…13 Previous research has shown improvements in discharge planning through system-level approaches that integrate health care and social work. 14 For example, Meo et al implemented daily multidisciplinary discharge rounds with physicians, nurses and social workers, using an electronic tracking tool to standardize information. 15 They noted a 21% reduction in length of stay without increased readmission rates.…”
mentioning
confidence: 99%
“…5 When patients eligible for OPAT finish therapy elsewhere, more hospital beds are available, which also shortens emergency department waiting times and increases the capacity to accept patient transfers. 6 In Belgium, 152 OPAT treatments resulted in avoidance of 3,153 days of hospitalization. 7 The critical importance of hospital capacity, especially flexibility and adaptability, is particularly highlighted in the era of the SARS-CoV-2 pandemic.…”
mentioning
confidence: 99%
“…7 The critical importance of hospital capacity, especially flexibility and adaptability, is particularly highlighted in the era of the SARS-CoV-2 pandemic. 6 Because inpatient care accounts for one-third of all healthcare spending in the United States, 6 utilizing subacute healthcare programs such as OPAT can bring many financial benefits to healthcare systems.…”
mentioning
confidence: 99%